Guantánamo diary - Slahi, Mohamedou Ould (Little, Brown and Company, 2015)
"An unprecedented international publishing event: the first and only diary written by a still-imprisoned Guantánamo detainee. Since 2002, Mohamedou Slahi has been imprisoned at the detainee camp at Guantánamo Bay, Cuba. In all these years, the United States has never charged him with a crime. Although he was ordered released by a federal judge, the U.S. government fought that decision, and there is no sign that the United States plans to let him go. Three years into his captivity Slahi began a diary, recounting his life before he disappeared into U.S. custody and daily life as a detainee. His diary is not merely a vivid record of a miscarriage of justice, but a deeply personal memoir--terrifying, darkly humorous, and surprisingly gracious. Published now for the first time, GUANTÁNAMO DIARY is a document of immense historical importance"--